A patch of positively charged residues regulates the efficacy of clinical DR5 antibodies in solid tumors - Gururaj Shivange (Elsevier, 2021)
Summary: Receptor clustering is the first and critical step to activate apoptosis by death receptor-5 (DR5). The recent discovery of the autoinhibitory DR5 ectodomain has challenged the long-standing view of its mechanistic activation by the natural ligand Apo2L. Because the autoinhibitory residues have remained unknown, here we characterize a crucial patch of positively charged residues (PPCR) in the highly variable domain of DR5. The PPCR electrostatically separates DR5 receptors to autoinhibit their clustering in the absence of ligand and antibody binding. Mutational substitution and antibody-mediated PPCR interference resulted in increased apoptotic cytotoxic function. A dually specific antibody that enables sustained tampering with PPCR function exceptionally enhanced DR5 clustering and apoptotic activation and distinctively improved the survival of animals bearing aggressive metastatic and recurrent tumors, whereas clinically tested DR5 antibodies without PPCR blockade function were largely ineffective. Our study provides mechanistic insights into DR5 activation and a therapeutic analytical design for potential clinical success.